Strategy for Awareness Creation among Rural Masses in the Aravalli Project: An Evaluation - Varma, V. K.; Srivastava, J. P. L. (Indian Forester, 1997)
The success of an eco-rehabilitation project, particularly when common lands are involved, largely depends upon eliciting cooperation of the local communities in providing effective protection to the treated area. A strategy for awareness creation among village communities, members of Village Forest Committees/Panchayat, project staff and school children was, therefore, designed and implemented with particular emphasis on women's involvement. An evaluation of the strategy was undertaken by a survey. The survey revealed that (1) a majority of the villagers had participated in the extension programmes, (2) they were aware of the project-interventions and concomitant flow of benefits, (3) a substantial proportion of the sampled population cooperated in protecting the plantations and were even keen to raise seedlings for the project, besides participating directly in the project activities. A welcome attitudinal change manifested in willingness to shoulder the responsibility of managing with the help of the Project staff the treated land when transferred to Panchayat. The acceptance of the idea of a Village Fund further shows that villagers are ready to contribute to the common cause of ceo-restoration of the Aravallis.